PENERAPAN METODE PEMBELAJARAN EXAMPLE NON EXAMPLE MATA PELAJARAN IPS DENGAN KOMPETENSI DASAR MENDESKRIPSIKAN HUBUNGAN ANTARA KELANGKAAN SUMBER DAYA DENGAN KEBUTUHAN MANUSIA YANG TIDAK TERBATAS GUNA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Tri Astindari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
Improving the quality of learning can be done by applying effective learning strategies or methods in the classroom, empower students and utilize the potential existing resources in school environment. Student’s activities in teaching and learning activities were characterized by the participation of students in carrying out the task which given by teacher. The result of this study indicate an increase in student’s learning outcomes, although Example non Example learning on the first cycle have not reached the minimum mastery criterion, so that Example non Example learning continued to the second cycle. The result of daily test analysis on the second cycle obtained classical completeness 87,5%, which indicates that the achievement of minimum mastery criterion. The conclusion of this study that the application of learning method by teacher greatly affects student’s learning activity and their learning outcomes. It is proved that the Example non Example learning can improve student’s learning activities and their learning outcomes in social science school subject on class VIII-V, with classical mastery degree 87,5%.